Crab nebula at 260 GHz with the NIKA2 polarimeter: Implications for the polarization angle calibration of future CMB experiments - Ritacco A.; Adam R.; Ade P.; Ajeddig H.; André P.; Artis E.; Aumont J.; Aussel H.; Beelen A.; Benoît A.; Berta S.; Bing L.; et al. (EPJ Web of Conferences, 2022)
The quest for primordial gravitational waves enclosed in the Cosmic Microwave Background (CMB) polarization B-modes signal motivates the development of a new generation of high sensitive experiments (e.g. CMBS4, LiteBIRD), thus allowing to probe the inflationary epoch in the early Universe. However, this will be only possible by ensuring a high control of the instrumental systematic effects and an accurate absolute calibration of the polarization angle. The Crab nebula is known to be a polarization calibrator on the sky for CMB experiments. Already used for the Planck satellite it exhibits a high polarized signal at microwave wavelengths. In this work we present Crab polarization observations obtained, in the 260 GHz frequency band, with the NIKA2 instrument. Furthermore, we discuss the accuracy needed on such a measurement to improve the constraints on the absolute angle calibration for CMB experiments.